Respuesta :
9514 1404 393
Answer:
a⁶b⁴
Step-by-step explanation:
The relevant rules of exponents are ...
(ab)^c = (a^c)(b^c)
(a^b)^c = a^(bc)
__
These let us simplify the expression as follows:
[tex](a^3b^2)^2=(a^3)^2(b^2)^2=a^{3\cdot2}b^{2\cdot2}=\boxed{a^6b^4}[/tex]
_____
Additional comment
It might be helpful to remember that an exponent signifies repeated multiplication.
a·a·a = a³ . . . . . . 'a' is a factor 3 times, so the exponent is 3.
Similarly, ...
(a³)² = (a³)·(a³) = (a·a·a)·(a·a·a) = a⁶